Non-noble metal gas diffusion anode, preparation thereof and application of non-noble metal gas diffusion anode in anion exchange membrane water electrolysis hydrogen production

By using catalytic active components such as nickel-based non-precious metal alloys and high-energy polymer binders in the anion exchange membrane water electrolysis system, a catalytic layer is formed to form a gas diffusion anode, which solves the problem of slow kinetics of oxygen precipitation reaction, and achieves a high-efficiency and low-energy consumption water electrolysis hydrogen production effect, and reduces costs.

CN119736655APending Publication Date: 2025-04-01SHANGHAI JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411902023.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In anion exchange membrane water electrolytic system, the kinetics of oxygen precipitation reaction are slower and require a higher overpotential to drive, which increases the energy consumption of the system.

Method used

A catalytic layer is constructed by using nickel-based non-noble metal alloys and nickel-based or alloy sulfides, nitrides, or phosphides or their derivatives as catalytic active components, combined with high-energy polymers such as polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin as binders, and a gas diffusion anode is formed on the conductive porous substrate.

Benefits of technology

It effectively improves the current density of hydrogen production by electrolysis of water, reduces energy consumption, and the cost is greatly reduced due to the use of non-precious metal materials, and the process is simple and scaleable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736655A_ABST
    Figure CN119736655A_ABST
Patent Text Reader

Abstract

The invention relates to a non-noble metal gas diffusion anode for anion exchange membrane water electrolysis hydrogen production and a preparation method of the non-noble metal gas diffusion anode. The gas diffusion anode is composed of a hydrophilic conductive substrate such as nickel felt or foamed nickel and a catalytic layer, and the catalytic layer takes nickel-based non-noble metal alloy and sulfide, nitride or phosphide of nickel-based or alloy as catalytic active components. High-energy polymers such as quaternized polystyrene, quaternized modified polynorbornene, polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin are used as binders, and a catalyst layer is formed on a substrate through a certain process, so that the gas diffusion anode is formed. The non-noble metal gas diffusion anode for hydrogen production through water electrolysis of the anion exchange membrane provided by the invention takes the non-noble metal as an active component, has the obvious advantages of high current density and strong stability compared with the similar technology, and can be applied to various anion exchange membrane water electrolysis electrochemical oxidation reactors or electrolytic tanks as anodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas diffusion electrodes, and specifically relates to a non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen and a preparation method thereof, and more particularly to a gas diffusion anode for water electrolysis electrochemical anodic oxidation using a nickel-based non-precious metal alloy and a nickel-based or alloy sulfide, nitride, or phosphide or their derivatives as catalytic active components and a preparation method thereof. Background Art

[0002] As the global demand for renewable energy and clean energy technologies grows, hydrogen energy, as a clean and efficient form of energy, has received widespread attention. Hydrogen production by water electrolysis is a technology that uses electrical energy to decompose water into hydrogen and oxygen, which has high energy conversion efficiency and is environmentally friendly.

[0003] Traditional water electrolysis technology usually uses alkaline electrolyzers, but there are problems such as high energy consumption and complex equipment maintenance. Anion exchange membrane water electrolysis technology has gradually become a research hotspot due to its advantages such as stable operation at higher pH values, low energy consumption, and simple equipment.

[0004] In anion exchange membrane water electrolysis system, the anode is mainly responsible for the oxygen evolution reaction, that is, water molecules lose electrons on the anode surface to generate oxygen and hydroxide ions. However, the kinetics of the oxygen evolution reaction are slow and require a high overpotential to drive, which increases the energy consumption of the system.

[0005] Therefore, developing efficient and stable anodes is the key to improving the performance of anion exchange membrane water electrolysis systems. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention relates to a non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen and a preparation method thereof.

[0007] The objective of the present invention is achieved through the following technical solutions:

[0008] The present invention provides a catalyst layer of a non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen, comprising a catalytically active component and a binder; the mass ratio of the catalytically active component to the binder is 1:5 to 5:1; the catalytically active component is selected from at least one of a nickel-based non-precious metal alloy and a nickel-based or alloy sulfide, nitride, or phosphide or their derivatives. .

[0009] Preferably, the nickel-based non-precious metal is selected from one or more of NixMyAz (M=Fe, Co, Al, Cr, Mo, A=N, P, S, B, x=0.4-0.8, y=0.6-0.2, z=0-0.1) nickel phosphide, nickel sulfide, nickel nitride, nickel boride and the like;

[0010] Preferably, the binder is selected from one or more of quaternized polystyrene, quaternary ammonium-modified polynorbornene, polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin.

[0011] Preferably, the mass ratio of the catalytically active component to the binder is 1:5 to 5:1.

[0012] Preferably, the mass of the binder is 15% to 85% of the total mass of the adhesive and the conductive agent.

[0013] The present invention also provides a method for preparing the above-mentioned catalyst layer, comprising the following steps:

[0014] a) mixing the catalytically active component and the binder to obtain a solid powder mixture;

[0015] b) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0016] c) coating the catalyst layer slurry onto a substrate and drying the catalytic layer.

[0017] Preferably, in step b), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1; the dispersant is selected from ultrapure water, anhydrous ethanol, isopropanol or n-butanol;

[0018] In step c), the coating method is selected from any one of air spraying, electrostatic spraying, ultrasonic spraying, blade coating, screen printing, and roller pressing.

[0019] The present invention also provides a non-noble metal gas diffusion anode for anion exchange membrane water electrolysis, comprising a conductive porous substrate and the above-mentioned catalyst layer.

[0020] Preferably, the conductive porous substrate is a composite structure obtained by adding a surface smoothing layer to one or more of foam nickel, foam zinc, foam iron, foam copper, foam nickel iron, and other foam alloys, titanium felt, nickel felt, stainless steel fiber felt, etc.

[0021] Preferably, the loading amount of the catalytically active component in the gas diffusion anode is 6 mg cm -2 ~20mg cm -2 The more preferred loading amount of the catalytically active component is 8 mg cm -2 ~16mg cm-2 .

[0022] The present invention also provides a method for preparing a non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen, comprising the following steps:

[0023] a1) mixing the catalytically active component and the binder to obtain a solid powder mixture;

[0024] b1) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0025] c1) The catalyst layer slurry is coated onto a conductive porous substrate, and then dried at 60-80° C. for 1-12 h to obtain a gas diffusion anode.

[0026] Preferably, in step b1), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1;

[0027] In step c1), the coating method is selected from any one of air spraying, electrostatic spraying, ultrasonic spraying, doctor blade coating, screen printing and roller pressing.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention proposes a non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen and a preparation method thereof. Compared with the prior art, the cost can be greatly reduced due to the use of non-precious metal materials as catalysts. On the other hand, in view of the problem of poor conductivity of the non-precious metal catalysts used, it is proposed to use foamed nickel, foamed zinc, foamed iron, foamed copper, foamed nickel-iron, and other foam alloys, titanium felt, nickel felt, stainless steel fiber felt and other conductive substrates to construct an electron channel, and use high-energy polymers such as polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin as a binder to achieve electrode forming while constructing a transmission channel for gas and liquid in the electrode, thereby effectively improving the current density of hydrogen production by electrolyzing water using the gas diffusion anode.

[0030] 2. The non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen proposed in the present invention uses non-precious metals as active components, has a simple electrode preparation process and can be scaled up, and has the obvious advantage of high operating current density compared with similar technologies. It can be used in various anion exchange membrane water electrolysis to produce hydrogen or in electrolytic cells as an anode.

[0031] The non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen proposed in the present invention uses non-precious metals as active components, has a simple electrode preparation process and can be scaled up, and has an obvious advantage of high current density compared with similar technologies. It can be used as an anode in various anion exchange membrane water electrolysis electrochemical oxidation reactors or electrolytic cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0033] Figure 1 Schematic diagram of the electrolytic cell structure (where the catalytic layers of the cathode and anode are placed closely to the anion exchange membrane);

[0034] Figure 2 This is a schematic diagram of the electrolytic cell test;

[0035] Figure 3 The current density of hydrogen production by water electrolysis at different electrolytic cell voltages for the non-precious metal gas diffusion anode and the precious metal anode obtained in Example 1.

[0036] Figure 4 The current density of hydrogen production by water electrolysis at different electrolytic cell voltages for the non-precious metal gas diffusion anode and the precious metal anode obtained in Example 2.

[0037] Figure 5 The current density of hydrogen production by water electrolysis at different electrolytic cell voltages for the non-precious metal gas diffusion anode and the precious metal anode obtained in Example 3. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0039] The following embodiment provides a catalyst layer of a non-noble metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen, comprising a catalytically active component and a binder;

[0040] The mass ratio of the catalytically active component to the conductive agent is 1:5 to 5:1;

[0041] The catalytically active component is selected from at least one of nickel-based non-precious metal alloys and nickel-based or alloy sulfides, nitrides, phosphides or their derivatives.

[0042] The catalyst layer of the gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen, the nickel-based non-precious metal compound is selected from one or more elements of NixMyAz (M = Fe, Co, Al, Cr, Mo, A = N, P, S, B, x = 0.4-0.8, y = 0.6-0.2, z = 0-0.1) nickel phosphide, nickel sulfide, nickel nitride, nickel boride, etc.;

[0043] The catalyst layer of the gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen, the binder is selected from one or more high-energy polymers such as quaternized polystyrene, quaternary ammonium modified polynorbornene, polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin.

[0044] The mass of the binder is 1% to 20% of the total mass of the adhesive and the conductive agent.

[0045] The method for preparing the catalytic layer comprises the following steps:

[0046] a) mixing the catalytically active component and the binder to obtain a solid powder mixture;

[0047] b) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0048] c) coating the catalyst layer slurry onto a substrate and drying the catalytic layer.

[0049] In step b), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1; the dispersant is selected from ultrapure water, anhydrous ethanol, isopropanol or n-butanol;

[0050] In step c), the coating method is selected from any one of air spraying, electrostatic spraying, ultrasonic spraying, blade coating, screen printing, and roller pressing.

[0051] The following embodiments also provide a non-precious metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen, comprising a conductive porous substrate and the aforementioned catalyst layer.

[0052] The conductive porous substrate is a composite structure obtained by adding a surface smoothing layer to one or more of foam nickel, foam zinc, foam iron, foam copper, foam nickel iron, and other foam alloys, titanium felt, nickel felt, stainless steel fiber felt, etc.

[0053] The gas diffusion anode has a catalytically active component loading of 6 mg cm -2 ~20mg cm -2 The more preferred loading amount of the catalytically active component is 8 mg cm -2 ~16mg cm -2 .

[0054] The method for preparing the non-noble metal gas diffusion anode for anion exchange membrane water electrolysis to produce hydrogen comprises the following steps:

[0055] a1) mixing the catalytically active component and the binder to obtain a solid powder mixture;

[0056] b1) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0057] c1) The catalyst layer slurry is coated onto a conductive porous substrate, and then dried at 60-80° C. for 1-12 h to obtain a gas diffusion anode.

[0058] In step b1), the mass ratio of the solid powder mixture to the dispersant is 10:1 to 200:1;

[0059] In step c1), the coating method is selected from any one of air spraying, electrostatic spraying, ultrasonic spraying, doctor blade coating, screen printing and roller pressing.

[0060] Under the above-mentioned parameter conditions, the non-noble metal gas diffusion anode for producing hydrogen by anion exchange membrane water electrolysis can be prepared.

[0061] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 ,like Figure 1 The structure of the conventional electrolytic cell used in the present application is shown, and the stacked arrangements from left to right are: end plate, annular insulating gasket, cathode (containing cathode catalyst, placed in the hollow chamber of the annular electrode frame), anion exchange membrane, anode (containing anode catalyst layer, placed in the hollow chamber of the annular electrode frame), annular insulating gasket, end plate, wherein the catalyst layers of the cathode and anode are placed facing the anion exchange membrane to form a zero-gap electrolytic cell (the catalyst layer is tightly fitted to the anion exchange membrane without gaps), and the test device is shown in FIG. Figure 2 As shown, the electrolyte is 1M KOH, the temperature is 60 °C, and the circulation flow rate is 15 mL min -1 The electrolyte flows out from the wide-mouth bottle placed in the water bath, flows through the anode side of the electrolytic cell, and adopts a bottom-in-top-out method. The electrolyte at the outlet of the electrolytic cell eventually flows back to the wide-mouth bottle in the water bath, thus forming a cycle for testing.

[0062] Example 1

[0063] A non-precious metal gas diffusion anode for anion membrane water electrolysis to produce hydrogen and a preparation method thereof, the steps are as follows:

[0064] 1) 400 mg Ni 0.4 Cr 0.5 B0.1 (Shanghai Hydrogen Technology Co., Ltd., NiCrB, particle size <50nm, the following table represents the atomic ratio of the corresponding metal in the alloy, with the number of atoms in the alloy as 1) and 100mg polynorbornene emulsion (Shanghai Hydrogen Technology Co., Ltd., model: 5wt% Norbornene) were uniformly mixed, and the proportion of polynorbornene to Ni 0.4 Cr 0.5 B 0.1 and polynorbornene accounted for 1.23% of the total mass, and then 35 mg of anhydrous ethanol was added to the solid powder mixture, and ultrasonic stirring was carried out at room temperature for 60 minutes to obtain a catalyst layer slurry.

[0065] 2) The catalyst layer slurry obtained above was ultrasonically sprayed onto one side of a sheet of foamed nickel (length * width * thickness: 20 * 20 * 0.5 mm, single side), and dried in an oven at 60 ° C for 12 h to obtain a gas diffusion anode containing a catalyst layer (Ni 0.4 Cr 0.5 B 0.1 The loading capacity is 15 mg cm -2 ).

[0066] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 The cathode used a Pt / C cathode with a Pt content of 40 wt% as the active component (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-40Pt / C-1), and the anode used the Ni 0.4 Cr 0.5 B 0.1 Gas diffusion anode or IrO2 anode as active ingredient (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-IrO2-1, particle size <50nm), produced by Dioxide Materials X37-50Grade RT is used as the separator between the cathode and anode. A DC power supply is used to test the polarization curve in the voltage range of 0-2.0V. Figure 3 The current density of hydrogen production by water electrolysis of the gas diffusion anode prepared in this embodiment is as known to all. When noble metals are used as cathodes and anodes, they have a smaller overpotential at low voltages, but are inferior to non-noble metal electrodes at high voltages and high current densities. Figure 3 It can be seen that using Ni 0.4 Cr 0.5 B 0.1 The current density of water electrolysis for hydrogen production using a gas diffusion anode can reach up to 2V@1.6Acm -2, especially at high current density, which is much higher than the current density of 2V@1.0A cm when IrO2 is used as the diffusion layer of the anode (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-IrO2-1). -2 , showing significant advantages.

[0067] Example 2

[0068] A non-precious metal gas diffusion anode for anion membrane water electrolysis to produce hydrogen and a preparation method thereof, the steps are as follows:

[0069] 1) 160 mg Ni 0.8 Al 0.1 P 0.1 Alloy (Shanghai Hydrogen Luan Technology Co., Ltd., NiAlP, particle size: 20-200nm) (0.8 and 0.1 represent the atomic number ratio of their corresponding metals in the alloy, with the number of atoms in the alloy as 1, particle size: 20-150nm) and 82mg polystyrene solution (5wt%) were uniformly mixed, with polystyrene accounting for 1% of NiAlP. 0.8 Al 0.1 P 0.1 2.5% of the total mass of the alloy and polystyrene, 350 mg of anhydrous ethanol was added to the solid powder mixture, and ultrasonic stirring was carried out at room temperature for 30 minutes to obtain a uniform catalyst layer slurry.

[0070] 2) The above catalyst layer slurry was sprayed onto a stainless steel fiber felt (Shanghai Hydrogen Luan Technology Co., Ltd., PHOENIX-05SS, single side) with a length*width*thickness=40*40*0.5mm using an electrostatic sprayer, with a deposition rate of 6mLmin -1 , effective area is 16cm 2 The gas diffusion cathode and anode containing the catalytic layer (Ni 0.8 Al 02 The alloy loading is 6 mg cm -2 ).

[0071] The process and conditions are the same as the above steps 1) and 2), except that 160 mg of Ni powder is mixed with Al powder and P powder (the materials are purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and the particle size range is 20-150 nm) in a molar ratio of 8:1:1 to replace Ni 0.8 Al 0.1 P 0.1 Alloy, the rest does not change, prepare powder gas diffusion anode, (where Ni 0.8 Al 0.1 P 0.1 The powder loading is 6 mg cm -2 )

[0072] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 The cathode used a Pt / C cathode with a Pt content of 40 wt% as the active component (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-40Pt / C-1), and the anode used the Ni 0.8 Al 02 Alloy gas diffusion anode or Ni 0.8 Al 02 Powder gas diffusion anode or IrO2 as the active ingredient anode (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-IrO2-1), the electrolyte is pure water, the pure water circulation flow rate is 30mL min -1 The temperature of pure water is 60℃, and the anode and cathode are circulated on both sides. Fumatech's FAAM-3-20um membrane is used as the anode and cathode diaphragm.

[0073] like Figure 4 As shown, the Ni prepared in this embodiment 0.8 Al 02 The reaction current density of the alloy gas diffusion anode in pure aqueous solution water electrolysis can reach 2V@450mA cm -2 , much higher than 2V@100mA cm in the same IrO2 anode pure water system -2 , and at the same time, much higher than Ni 0.8 Al 02 Powder in the same pure water system 2V@45mA cm -2 This proves that the gas diffusion anode proposed in the present invention also has a higher current density in pure aqueous solution.

[0074] Example 3

[0075] A non-precious metal gas diffusion anode for anion membrane water electrolysis to produce hydrogen and a preparation method thereof, the steps are as follows:

[0076] 1) 20 mg NiFe2S4 (Shanghai Hydrogen Technology Co., Ltd., NiFeS, particle size, <50 nm), 60 mg Ni 0.6 Al 0.4 (0.6 and 0.4 represent the atomic ratio of their corresponding metals in the alloy, with the number of atoms in the alloy as 1, and the particle size range is 30-100nm) and 80mg polytetrafluoroethylene emulsion (5wt%), polytetrafluoroethylene accounts for NiFe2S4, Ni 0.6 Al 04 and 4.8% of the total mass of polytetrafluoroethylene, and mixed evenly, then 36 mg of anhydrous ethanol was added to the obtained solid powder mixture, and ultrasonically stirred at room temperature for 60 minutes to obtain a catalyst layer slurry.

[0077] 2) The above catalyst layer slurry was printed onto nickel foam by screen printing, with an effective area of ​​length * width * thickness = 15 * 15 * 0.5 mm (single-side coating). Drying was carried out in an oven at 60°C for 2 h to obtain a gas diffusion cathode containing a catalyst layer (where the anode loading was 20 mg cm -2 ).

[0078] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 The cathode uses a Pt / C cathode with a Pt content of 40wt% as the active component (Shanghai Hydrogen Technology Co., Ltd., model: PHOENIX-40Pt / C-1), the anode uses the above-prepared gas diffusion anode or an anode with IrO2 as the active component (Shanghai Hydrogen Technology Co., Ltd., model: PHOENIX-IrO2-1) The electrolyte uses 1MKHCO3, and the flow rate is 20mLmin -1 The temperature is 60℃, and the cathode and anode are circulated on both sides. The anion exchange membrane (PHOENIX-30um) of Shanghai Hydrogen Technology Co., Ltd. is used to separate the two stages. Figure 5 As shown, the water electrolysis current density can reach 2V@480mA cm -2 Much higher than the 2V@200mA cm of the 1MKHCO3 system of similar IrO2 anode -2 , which shows that the gas diffusion anode has a high current density in different electrolytes.

[0079] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A non-precious metal gas diffusion anode, comprising a substrate and a catalytic layer attached to one or both sides of the substrate, characterized in that: The catalytic layer includes catalytically active components and a binder; The catalytically active component is selected from at least one or more of a nickel-based non-precious metal alloy or a sulfide, nitride, or phosphide of a nickel-based non-precious metal alloy or a derivative thereof.

2. The non-precious metal gas diffusion anode according to claim 1, characterized in that: The composition of the catalytic active component is NixMyAz, wherein: M = one or more of Fe, Co, Al, Cr or Mo, A = one or more of N, P, S or B, x = 0.4-0.8 (preferably 0.45-0.75, more preferably 0.50-0.70), y = 0.6-0.2 (preferably 0.55-0.25, more preferably 0.50-0.30), z = 0.001-0.1 (preferably 0.001-0.008, more preferably 0.002-0.005).

3. The non-precious metal gas diffusion anode according to claim 1, characterized in that: The binder is selected from one or more of quaternized polystyrene, quaternized polynorbornene, polynorbornene, polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin.

4. The non-precious metal gas diffusion anode according to claim 1, characterized in that: In the catalytic layer, the mass of the binder is 1% to 20% (preferably 1% to 10%, more preferably 1% to 5%) of the total mass of the binder and the catalytically active components.

5. The non-precious metal gas diffusion anode according to claim 1, characterized in that: The substrate is a conductive porous substrate, which can be foam alloys such as foam nickel, foam zinc, foam iron, foam copper, foam nickel iron, and one or more of titanium felt, nickel felt, stainless steel fiber felt, and the like.

6. The non-precious metal gas diffusion anode according to claim 1 or 5, characterized in that: The gas diffusion anode has a catalytically active component loading of 6 mg cm -2 ~20mg cm -2 The preferred loading amount of the catalytically active component is 8 mg cm -2 ~16mg cm -2 .

7. A method for preparing a non-precious metal gas diffusion anode according to any one of claims 1 to 6, characterized in that: The following steps are involved: a) mixing a catalytically active component and a binder to obtain a mixture; b) adding a dispersant to the solid powder mixture to obtain a catalyst layer slurry; c) coating the catalyst layer slurry onto one or both surfaces of the sheet-like substrate and drying the slurry to obtain the catalyst layer.

8. The preparation method according to claim 7, characterized in that: In step b), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1; the dispersant is selected from one or more of deionized water, anhydrous ethanol, isopropanol or n-butanol; In step c), the coating method is selected from any two or more of air spraying, electrostatic spraying, ultrasonic spraying, scraping, screen printing, and roller pressing; the drying temperature is 60-80° C. and the time is 1-12 hours.

9. Use of the non-precious metal gas diffusion anode according to any one of claims 1 to 6 as an anode in an anion exchange membrane water electrolysis hydrogen production or an anion exchange membrane water electrolysis electrochemical oxidation reactor.

Citation Information

Patent Citations

  • Membrane electrode for proton exchange membrane water electrolysis battery and preparation thereof

    CN101388463A

  • AEM anode slurry and preparation method of membrane electrode of AEM anode slurry

    CN118207566A

  • Method And Device for Behavior Recognition in Environment with Various Perspective Distortions

    KR1020250059078A

  • Apparatus for recognizing object and method thereof

    KR1020250106766A

  • Toilet bowl sterilization device of a bidet

    KR1020260000906A